Breast Implant-Associated Immunological Disorders - Lily J. Suh; Imran Khan; Christine Kelley-Patteson; Ganesh Mohan; Aladdin H. Hassanein; Mithun Sinha (Journal of Immunology Research)
Background. Breast implants are commonly placed postbreast cancer reconstruction, cosmetic augmentation, and gender-affirming surgery. Breast implant illness (BII) is a systemic complication associated with breast implants. Patients with BII may experience autoimmune symptoms including fatigue, difficulty concentrating, hair loss, weight change, and depression. BII is poorly understood, and the etiology is unknown. The purpose of this literature review is to characterize BII autoimmune disorders and determine possible causes for its etiology. Methods. The PubMed, Google Scholar, Embase, Web of Science, and OVID databases were interrogated from 2010 to 2020 using a query strategy including search term combinations of “implants,” “breast implant illness,” “autoimmune,” and “systemic illness.” Results. BII includes a spectrum of autoimmune symptoms such as fatigue, myalgias/arthralgias, dry eyes/mouth, and rash. A review of epidemiological studies in the past ten years exhibited evidence affirming an association between breast implants and autoimmune diseases. The most commonly recognized were Sjogren’s syndrome, rheumatoid arthritis, systemic sclerosis, chronic fatigue syndrome, and Raynaud’s syndrome. Explantation resulted in alleviation of symptoms in over 50% of patients, strengthening the hypothesis linking breast implants to BII. Studies have shown that silicone is a biologically inert material and unlikely to be the cause of these symptoms. This is supported by the fact that increased risk of autoimmune disease was also reported in patients with other implantable biomaterials such as orthopedic implants. Recent studies shed light on a possible role of bacterial biofilm and subsequent host-pathogen interactions as a confounding factor to this problem. Conclusion. BII could be dependent on biofilm infection and the microenvironment around the implants. The true pathophysiology behind these complaints must be further investigated so that alternative treatment regimens other than explantation can be developed. Translational significance of these studies is not limited to breast implants but extends to other implants as well.